PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN UIN SUNAN KALIJAGA YOGYAKARTA - Yani Tri Wijayanti (Profetik: Jurnal Komunikasi, 2013)
Transformation IAIN (State Islamic Institute) Sunan Kalijaga become the UIN (State Islamic University) Sunan Kalijaga demanding reform, one area of human resources governance. Human resources to be one important factor for the sustainability of the activity in the UIN Sunan Kalijaga. This study focuses on the services provided by employees (personal administration). In its implementation on the ground was still found how the performance of employees at UIN Sunan Kalijaga have not maximum and satisfyyet. Based on this background, this study proposed the formulation of the problem as follows : Is there any influence of organizational culture on the employee performance in UIN Sunan Kalijaga Yogyakarta? The methode which is which used is a quantitatively method. The population of this study is overall of UIN Sunan Kalijaga employees totaling 498 people, with a sample of 222 respondents. Research location is UIN Sunan Kalijaga Yogyakarta.Techiques of data collection is done by providing the questionaire as the primary data. From the reasearch that been done obtained the following results : First, the relationship between the culture of the organization with employee performance by 0.619, direction and significant. Secondly, the influence of the frequency of organizational culture on employee performance by 38,3%. The remaining 61.7% are influenced by factors beyond regression models. Third, because the affected employee performance trend of organizationalculture in general has decreased.